MULTIDISCIPLINARY GEOPHYSICAL OBSERVATIONS AT THE PETROPAVLOVSK SITE, KAMCHATKA - Balesta S.T.; Kopylova G.N.; Latypov E.R.; Kuzmin Y.D. (My University, 2000)
In 1995-1998 the Kamchatkan Experimental Seismological Team (KEST), Geophysical Service (GS), Russian Academy of Sciences (RAN) conducted, in cooperation with other research and production organizations, organizational-technical and methodological work to set up an automated system for multidisciplinary geophysical observations as a basis for earthquake prediction in Kamchatka. This paper is an account of the present-day condition of a geophysical network for earth-current, electromagnetic, ground water, and other observations at the Petropavlovsk Site and of the data acquisition and processing system based on the KEST GS RAN facilities. The potential of the currently operated geophysical observation system for identification of earthquake precursors is discussed using seismic events of 1997-1998 as examples.